2016
DOI: 10.1159/000453148
|View full text |Cite|
|
Sign up to set email alerts
|

Jagged1/Notch3 Signaling Modulates Hemangioma-Derived Pericyte Proliferation and Maturation

Abstract: Background: The Notch signaling pathway has been implicated in the pericyte phenotype, but its exact roles in hemangioma-derived pericytes (Hem-pericytes) remain ill defined. Methods: Hem-pericytes were stimulated by immobilized recombinant Jagged1. The potential mechanisms of Notch-induced Hem-pericytes growth arrest were investigated by cell cycle assay, and the role of the Notch in promoting Hem-pericyte maturation was also analyzed by real-time PCR and western blot. Results: Activation of Notch3 in Hem-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…The role of the Notch pathway in cancers has been determined according to the effect of Notch pathway on cell proliferation, migration, and invasion [22][23][24][25][26]. In the present study, we demonstrated that TRIM67 overexpression can upregulate Notch1, Jagged1, and NICD.…”
Section: Discussionsupporting
confidence: 58%
“…The role of the Notch pathway in cancers has been determined according to the effect of Notch pathway on cell proliferation, migration, and invasion [22][23][24][25][26]. In the present study, we demonstrated that TRIM67 overexpression can upregulate Notch1, Jagged1, and NICD.…”
Section: Discussionsupporting
confidence: 58%
“…This multipotency is analogous to cells belonging to the heterogeneous multipotent stromal population previously referred to as "mesenchymal stem cells" but more commonly described now as "mesenchymal progenitors." In fact, cultured pericytes display broader multipotency compared to mesenchymal progenitors, including differentiation into vascular smooth muscle cells, myofibroblasts as well as parenchymal cells such as skeletal and cardiac myocytes and neuronal cells (Barron et al, 2016;Ji et al, 2016;Birbrair et al, 2017;Siedlecki et al, 2018;Alarcon-Martinez et al, 2019). The broad multipotency reported for pericytes is the basis on which some researchers postulate that pericytes are the predominant source of tissue resident mesenchymal progenitors (Crisan et al, 2008;da Silva Meirelles et al, 2008).…”
Section: Activation Multipotency and Fate Specificity Of Pericytesmentioning
confidence: 99%
“…Besides the regulation imposed by cell adhesion molecules, pericyte quiescence is promoted by Notch signaling. Notch3 on pericytes interacts directly with Jagged-1 on endothelial cells to promote pericyte-endothelial cell adhesion while also inhibiting pericyte proliferation and migration (Liu et al, 2009(Liu et al, , 2010Schulz et al, 2015;Ji et al, 2016). Notch signaling is implicated in the regulation of quiescence and metabolism in many cell types (Iso et al, 2003;Liu et al, 2010;Koch et al, 2013), through diverse actions that include downregulated expression of glycolytic enzymes such as PFKFB3 (De Bock et al, 2013;Bayin et al, 2017).…”
Section: Quiescencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some results indicated that Notch-3 inhibition could help enhance the sensitivity to paclitaxel [ 38 , 39 ]. Recent findings have suggested that the Notch pathway is one of the most important signal pathways in tumor development or progression [ 40 ]. Overall, other results also have proved that Notch-3 protein significantly affects the development and prognosis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%